The Champa Pillar (1035 CE) and its possible connection with the Turkic dynasties - Muhammad Uzair Ismail,; Zuliskandar Ramli,; Ros Mahwati Ahmad Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Physical objects in the forms of pillar and tombstone of Muslims migrants who came to Southeast Asia are of tremendous significance as they are the earliest seeing evidence which indicates Muslim presence in the region. However, the artistic dimensions of these objects are less studied compared to the inscription and material. Therefore, this study intends to investigate the connection between the earliest Islamic evidence found in the Southeast Asia region, the Champa Pillar (1035 CE) and its artistic influence. The art historical method was used in this study to analyse the development and influence of the Islamic art in the region based on style, technique and composition. Based on the analysis, the artistic repertoire in terms of the calligraphy script together with the content of the inscription show a strong connection with the Turkic people from India, particularly the Ghaznavid Dynasty (977-1186 CE). In addition to this, the content is also historically accurate with the development of Islamic Dynasties in the west in terms of event, historical figures and their migration. This suggest that Muslims of Turkic stock from the Ghaznavid Dynasty were among the earliest to migrate to Southeast Asia and settled in Champa, where they established an art guild and their Turkic-Islamic artistic repertoires later influenced the local existing Malay art. This indicates that while the Arabs and Persians were responsible for the spread of Islam, the Turkic people had a role in spreading the Islamic artistic repertoires to Southeast Asia.